2004
DOI: 10.1074/jbc.m311365200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Hormone-sensitive Lipase Isoform Expressed in Pancreatic β-Cells

Abstract: Hormone-sensitive lipase (HSL) is a key enzyme in fatty acid mobilization in many cell types. Two isoforms of HSL are known to date, namely HSL adi (84 kDa in rat) and HSL tes (130 kDa in rat). These are encoded by the same gene, with exons 1-9 encoding the parts that are common to both and an additional 5 -exon encoding the additional amino acids in HSL tes . HSL of various tissues, among these the islet of Langerhans, is larger than HSL adi , but not as large as HSL tes , indicating that there may be other 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 35 publications
2
42
1
Order By: Relevance
“…Had we corrected for total insulin content in the in vitro secretion experiments, thus presenting the data as fractional insulin release, then not only early but also later phases of insulin secretion would appear as impaired. Recent work has shown that HSL is located in close proximity to the secretory granules in the pancreatic beta cell [45]. Our present findings therefore provide a functional correlate of this compartmentation of HSL.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Had we corrected for total insulin content in the in vitro secretion experiments, thus presenting the data as fractional insulin release, then not only early but also later phases of insulin secretion would appear as impaired. Recent work has shown that HSL is located in close proximity to the secretory granules in the pancreatic beta cell [45]. Our present findings therefore provide a functional correlate of this compartmentation of HSL.…”
Section: Discussionsupporting
confidence: 62%
“…The association of HSL with the secretory granules provides a structural correlate for these mechanisms [45]. Future work should focus on the identity of the lipid signals generated by HSL and perhaps other lipases in the beta cell.…”
Section: Discussionmentioning
confidence: 99%
“…We showed impaired GSIS in only male fasted Hsl −/− mice, and this was completely reversed by the provision of exogenous NEFA [18]. The expression of HSL in beta cells, however, has been shown to be upregulated by a prolonged high glucose concentration [32] and HSL has been shown to be co-localised with insulin granules [33]. There has been particular interest in the role of non-HSL lipases in adipose tissue metabolism [34,35].…”
Section: Discussionmentioning
confidence: 87%
“…During the search for a stimulatory protein, CREB was excluded since the LIPE promoter does not contain a cAMP-response element (CRE) (Smale 1997, Lindvall et al 2004. The best candidate for such a protein was SF-1, a principal stimulator of expression of almost all genes involved in steroid hormone synthesis (Val et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…HSL is most active in adipose tissue. In steroidogenic tissues including the adrenal cortex, the enzyme is about three times less active, and its activity in pancreatic b-cells is even lower, while in the heart and macrophages, it is negligible (Khoo et al 1993, Langfort et al 1999, Lindvall et al 2004.…”
Section: Introductionmentioning
confidence: 99%